WAQF IN A NON-MUSLIM COUNTRY: A PRELIMINARY SURVEY OF WAQF IN THAILAND - Tawat Noipom; Aris Hassama (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2017)
Waqf in various forms has been found in Muslim communities throughout Thailand. However, a small number of systematic inquiries has been conducted to document basic information such as forms, management, and impacts of waqf in the country. As a result of that, it is difficult to further investigate whether waqf serves its objectives of socio-economic development of Muslim communities or otherwise. This study, therefore, aims at preliminary examining the forms, management, and issues on waqf in the Muslim majority area of Satun province in the south of Thailand. In order to arrive at the conclusion, a qualitative approach was employed. In-depth interview was used to gather information from Imans. Purposive sampling technique was used to choose the interviewees who have adequate knowledge on the topic. Narrative analysis was the method of analyzing the collected data. The findings in this study show that waqf in Thailand can be found in various forms and mainly property waqf which includes mosque buildings, Islamic schools, agricultural land and rental houses. Cash can also be found as a part of the process to purchase of waqf properties. These waqf properties are managed by mosque committee but are not required to report to the Provincial Islamic Committee. As a result, the information on the value of waqf cannot be found anywhere. The willingness of waqf contributors and no provisions of the law are the two main issues confronting waqf management in Thailand. This paper provides basic waqf information in Thailand and leads the way for further studies and subsequently effective model of waqf in a non-Muslim country. =========================================== Wakaf dalam berbagai bentuk telah ditemukan dalam komunitas Muslim di seluruh Thailand. Namun, sejumlah kecil pertanyaan sistematis telah dilakukan untuk mendokumentasikan informasi dasar seperti bentuk, manajemen dan dampak dari wakaf di negara tersebut. Sebagai hasil dari itu, sulit untuk menyelidiki lebih lanjut apakah wakaf dilaksanakan sesuai tujuannya untuk pembangunan sosial-ekonomi masyarakat Muslim atau sebaliknya. Oleh karena itu penelitian ini bertujuan untuk melakukan pemeriksaan awal terhadap bentuk, manajemen, dan isu-isu tentang wakaf di wilayah mayoritas Muslim di provinsi Satun di Thailand selatan. Dalam rangka penarikan kesimpulan, dilakukan pendekatan kualitatif. Wawancara mendalam digunakan untuk mengumpulkan informasi dari para Imam. Teknik purposive sampling digunakan untuk memilih responden yang memiliki pengetahuan yang memadai mengenai topik ini. Analisis naratif adalah metode analisis terhadap data yang telah dikumpulkan. Hasil penelitian ini menunjukkan bahwa wakaf di Thailand dapat ditemukan dalam berbagai bentuk dan terutama wakaf properti yang meliputi bangunan masjid, sekolah-sekolah Islam, lahan pertanian dan rumah sewa. Kas juga dapat ditemukan sebagai bagian dari proses untuk membeli properti wakaf. Wakaf properti ini dikelola oleh komite masjid, tetapi tidak diharuskan untuk melapor ke Komite Islam Provinsi. Akibatnya, informasi tentang nilai wakaf tidak dapat ditemukan dimanapun. Kesediaan kontributor wakaf dan tidak ada ketentuan hukum adalah dua isu utama yang dihadapi manajemen wakaf di Thailand. Penelitian ini memberikan informasi wakaf dasar di Thailand dan membuka jalan untuk studi lebih lanjut dan model wakaf yang efektif setelah ini di negara non-Muslim.